Recent progress in the research of cold-inducible RNA-binding protein. (4th October 2017) - Zhong, Peng; Huang, He
Cold-inducible RNA-binding protein (CIRP) is a cold-shock protein which can be induced after exposure to a moderate cold-shock in different species ranging from amphibians to humans. Expression of CIRP can also be regulated by hypoxia, UV radiation, glucose deprivation, heat stress and H2 O2, suggesting that CIRP is a general stress-response protein. In response to stress, CIRP can migrate from the nucleus to the cytoplasm and regulate mRNA stability through its binding site on the 3′-UTR of its targeted mRNAs. Through the regulation of its targets, CIRP has been implicated in multiple cellular process such as cell proliferation, cell survival, circadian modulation, telomere maintenance and tumor formation and progression. In addition, CIRP can also exert its functions by directly interacting with intracellular signaling proteins. Moreover, CIRP can be secreted out of cells. Extracellular CIRP functions as a damage-associated molecular pattern to promote inflammatory responses and plays an important role in both acute and chronic inflammatory diseases. Here, we summarize novel findings of CIRP investigation and hope to provide insights into the role of CIRP in cell biology and diseases. Lay abstract: Cold-inducible RNA-binding protein is a protein that can be be regulated by a variety of stress factors, such as cold temperature and UV radiation. Its response to stress is implicated in multiple cellular process such as cell proliferation, cell survival, circadian modulation, telomere maintenance and tumor formation and progression. It can also travel outside the cell where it can be involved in inflammatory diseases. This review summarizes our current knowledge of cold-inducible RNA-binding protein and its actions, what we have yet to understand and its potential for use in treatment of diseases ranging from cancer to diabetes.